Analysis and Monitoring of Changes in Land Cover and Land Uses in Al-Dhuluiyah District for the Period (2001-2024) - Ali Hamoud, Ahmed Hassan; Sabaa Al-Subaihi, Ali Mukhlef (Journal of Tikrit University for Humanities, 2025)
This study aims to analyze and monitor changes in land cover and land use in the Al-Dhuluiyah district, providing a detailed picture of desertification. This study utilizes map design and modern GIS technologies for the period (2001-2024). Using geographic techniques and satellite imagery, and using wave classification, four indicators were designed for the study area (vegetation cover index, soil salinity index, biological crust index, and soil degradation index). The period under study reveals a decline and deterioration in land cover. This is due to the study area suffering from drought, and the poor practices that have led to large areas of green land being cut down. The analysis results showed a significant decline in vegetation cover due to drought on one hand, and incorrect human practices on the other, such as the removal of natural vegetation for urban expansion. An increase in residential areas was also observed compared to previous periods, indicating the impact of natural factors and human activities on land degradation and the expansion of desertification